Draft Genome Sequences of 510 Listeria monocytogenes Strains from Food Isolates and Human Listeriosis Cases from Northern Italy - Lomonaco, Sara (Genome Announc, 2018)
Listeriosis outbreaks are frequently multistate/multicountry outbreaks, underlining the importance of molecular typing data for several diverse and well-characterized isolates. Large-scale whole-genome sequencing studies on Listeria monocytogenes isolates from non-U.S. locations have been limited. Herein, we describe the draft genome sequences of 510 L. monocytogenes isolates from northern Italy from different sources.